Population Structure and Genotype–Phenotype Associations in a Collection of Oat Landraces and Historic Cultivars - Winkler, Louisa R.; Michael Bonman, J.; Chao, Shiaoman; Admassu Yimer, B.; Bockelman, Harold; Esvelt Klos, Kathy (Frontiers in Plant Science, 2016)
Population structure and genetic architecture of phenotypic traits in oat (Avena sativa L.) remain relatively under-researched compared to other small grain species. This study explores the historic context of current elite germplasm, including phenotypic and genetic characterization, with a particular focus on identifying under-utilized areas. A diverse panel of cultivated oat accessions was assembled from the USDA National Small Grains Collection to represent a gene pool relatively unaffected by twentieth century breeding activity and unlikely to have been included in recent molecular studies. The panel was genotyped using an oat iSelect 6K beadchip SNP array. The final dataset included 759 unique individuals and 2,715 polymorphic markers. Some population structure was apparent; with the first three principal components accounting for 38.8% of variation and 73% of individuals belonging to one of three clusters. One cluster with high genetic distinctness appears to have been largely overlooked in twentieth century breeding. Classification and phenotype data provided by the Germplasm Resources Information Network were evaluated for their relationship to population structure. Of the structuring variables evaluated, improvement status (cultivar or landrace) was relatively unimportant, indicating that landraces and cultivars included in the panel were all sampled from a similar underlying population. Instead, lemma color and region of origin showed the strongest explanatory power. An exploratory association mapping study of the panel using a subset of 2,588 mapped markers generated novel indications of genomic regions associated with awn frequency, kernels per spikelet, lemma color and panicle type. Further results supported previous findings of loci associated with barley yellow dwarf virus tolerance, crown rust (caused by Puccinia coronata f. sp. avenae) resistance, days to anthesis and growth habit (winter/spring). In addition, two novel loci were identified for crown rust resistance.